2021
DOI: 10.1007/s00432-021-03644-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of lung and gut microbiota on lung cancer pathogenesis

Abstract: Background Lung cancer is the leading cause of cancer-related deaths worldwide (Ferlay et al., Int J Cancer 136:E359–386, 2015). In addition, lung cancer is associated with the highest mortality among all cancer types (Wu et al., Exp Ther Med 16:3004–3010, 2018). Previous studies report that microbiota play an important role in lung cancer. Notably, changes in lung and gut microbiota, are associated with progression of lung cancer. Several studies report that lung and gut microbiome promote lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 75 publications
0
102
0
1
Order By: Relevance
“…Apart from gastroesophageal content inhalation and sputum swallowing, which can partially explain this inter-organ connection, the GLA also involves indirect communications: gut and lung microbes show similar colonization characteristics in the early stages of life, and the gut and lungs have a strong mucosal defense system against microbes [ 3 ]. It is reported that short-chain fatty acids (SCFAs), which are the major metabolic products of the GM from dietary fiber (especially in case of a high-fiber diet), act in the lungs as signaling molecules on resident antigen-presenting cells to attenuate the inflammatory and allergic responses [ 57 ].…”
Section: The Human Microbiomementioning
confidence: 99%
See 4 more Smart Citations
“…Apart from gastroesophageal content inhalation and sputum swallowing, which can partially explain this inter-organ connection, the GLA also involves indirect communications: gut and lung microbes show similar colonization characteristics in the early stages of life, and the gut and lungs have a strong mucosal defense system against microbes [ 3 ]. It is reported that short-chain fatty acids (SCFAs), which are the major metabolic products of the GM from dietary fiber (especially in case of a high-fiber diet), act in the lungs as signaling molecules on resident antigen-presenting cells to attenuate the inflammatory and allergic responses [ 57 ].…”
Section: The Human Microbiomementioning
confidence: 99%
“…In summary, the GLA immune interplay is a bidirectional two-way process resulting from multifaceted interactions among the different microbial components of both the gut and lung microbiota, together with local and distal immune effects. Changes in this axis may lead to harmful outcomes, such as cancer development, pathogen colonization, damage of tissue, and increased susceptibility to infections [ 3 ].…”
Section: The Human Microbiomementioning
confidence: 99%
See 3 more Smart Citations